Level Of Knowledge Of Sports Injury Using PRICES Method On Physical Education Students - Rizki Kurniati; Epi Supriyani Siregar; Bogy Restu Ilahi (UNIB Press, 2022)
The purpose of this study was to determine the knowledge of physical education students about sports injuries using the PRICES method at UPMI Medan. This research is a descriptive study, with data collection techniques using survey methods. The research instrument uses a knowledge test in the form of true-false. The population in this study was 40 students of the Physical Education Program. The data analysis technique used descriptive with percentage. The results showed that: very high category of 22.50% (9 people), high category of 35% (14 people), moderate category of 25% (10 people), low category of 13% (5 people), and very low by 5% (2 people). These results can be concluded that the knowledge of physical education program students about early handling of sports injuries using the PRICES (Protect Rest Ice Compression Elevation Support) method at UPMI Medan is in the high category.